An overview of dental implant biomaterials - Ravi, Rama Krishna; Ganta, Gopala Krishna; Rajesh, Nallakunta; Duvvuri, Satyanarayana Reddy; Sesha Reddy, P; Reddy, Raghavendra Prasad (International Journal of Dental Materials, 2022)
Regardless of stomatognathic system atrophy, illness, or injury, modern dentistry endeavours to restore the patient to normal shape, function, comfort, aesthetics, speech, and health. Predictable success is now a reality for the rehabilitation of many difficult conditions as a result of ongoing research in treatment planning, implant designs, materials, and methodologies. The medical fields have long placed a strong emphasis on the biocompatibility properties of synthetic materials (biomaterials) used to replace biological tissues. In addition, implant biomaterials must be suitable in terms of mechanical strength, biocompatibility, and structural biostability in order to function at their best. In this article, the various implant biomaterials with their properties and applicability to implant dentistry are discussed.